Biochemistry may be misleading in metachronous MEN2A-associated phaeochromocytoma following unilateral total adrenalectomy. Issue 6 (11th June 2020) - Nassour, Anthony-Joe; Nylen, Carolina; Sywak, Mark; Clifton-Bligh, Roderick
Abstract : A 63-year-old woman with multiple endocrine neoplasia type 2A (MEN2A) presented with recurrent spells of headaches, sweats and palpitations decades after right adrenalectomy for phaeochromocytoma, and total thyroidectomy for medullary thyroid cancer. She was hypertensive and in sinus rhythm. DOTA-TATE positron-emission tomography (PET) demonstrated a 12mm enhancing left adrenal incidentaloma. 24 hours urine catecholamines, and multiple plasma metanephrine and normetanephrine measurements were all within normal reference ranges. Based on her symptoms and imaging findings, left adrenalectomy was performed and found a 40 mm phaeochromocytoma. Her symptoms have since completely resolved and plasma metanephrine is now undetectable MEN2-associated phaeochromocytomas are often bilateral and may be metachronous. Patients at high risk of phaeochromocytoma who develop symptoms of catecholamine excess should be carefully evaluated even if plasma or urinary metanephrines are within the normal reference range. Biochemical reference ranges for metanephrines need to be adjusted accordingly in patients who have had prior unilateral total adrenalectomy.